Improving Curcumin Bioavailability: Current Strategies and Future Perspectives - Rita Tabanelli; Simone Brogi; Vincenzo Calderone (Pharmaceutics, 2021)
Curcumin possesses a plethora of interesting pharmacological effects. Unfortunately, it is also characterized by problematic drug delivery and scarce bioavailability, representing the main problem related to the use of this compound. Poor absorption, fast metabolism, and rapid systemic clearance are the most important factors contributing to low curcumin levels in plasma and tissues. Accordingly, to overcome these issues, numerous strategies have been proposed and are investigated in this article. Due to advances in the drug delivery field, we describe here the most promising strategies for increasing curcumin bioavailability, including the use of adjuvant, complexed/encapsulated curcumin, specific curcumin formulations, and curcumin nanoparticles. We analyze current strategies, already available in the market, and the most advanced technologies that can offer a future perspective for effective curcumin formulations. We focus the attention on the effectiveness of curcumin-based formulations in clinical trials, providing a comprehensive summary. Clinical trial results, employing various delivery methods for curcumin, showed that improved bioavailability corresponds to increased therapeutic efficacy. Furthermore, advances in the field of nanoparticles hold great promise for developing curcumin-based complexes as effective therapeutic agents. Summarizing, suitable delivery methods for this polyphenol will ensure the possibility of using curcumin-derived formulations in clinical practice as preventive and disease-modifying therapeutics.